RELATIONSHIP BETWEEN THE USE OF TIKTOK AND THE LOSS OF SHYDNESS IN BANYUAJUH 6 ELEMENTARY SCHOOL - Rosideh Rosideh; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This research was conducted to determine the extent of the relationship between the use of tiktok and the loss of the culture of shame in children. The method used in this research is descriptive qualitative. In collecting data, the researcher gave a questionnaire to 28 children and the interviews were conducted at the students' homes. The interviewees were children who like to make tiktok videos. Results from 28 respondents obtained regarding how many children use the tiktok application and the intensity of children in using the tiktok application. After being analyzed, it turned out that there were 22 children who used the tiktok application and 6 children who had never used tiktok. Of the 22 children who use the tiktok application, it turns out that 13 children like to make videos on tiktok and 9 children only see other people's videos on the tiktok application. The results of the study show that 79% of children use tiktok more. Of the 78% of students who use the tiktok application, the intensity of dancing in making tiktok videos reaches 47% of children dancing in making videos on tiktok and 32% of children only see videos on tiktok. The results of the discussion show that there is a relationship between the use of tiktok and a child's culture of shame. This is likely due to a lack of parental supervision.